PENGARUH IKLIM ORGANISASI, ETOS KERJA DAN KEMAMPUAN INDIVIDUAL TERHADAP KINERJA KARYAWAN PADA PT. DOS NI ROHA DISTRIBUTION CABANG MEDAN - Purba, Jarison; Purba, Betniar (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to determine and explain the influence of organizational climate, work ethic and individual abilities on employee performance at PT. DNR Distribution Medan Branch. The total population in this study was 72 employees and the sample size used a purposive sampling technique, namely those related to sales with a total of 60 people. The analysis techniques used in this research are validity and reliability tests, classical assumptions, multiple linear regression, t test, F test, and determinant coefficient (R2) using SPSS Version 25.. The research results show that there is an influence between the independent variables, namely organizational climate, work ethic and individual ability, on the dependent variable, namely employee performance. From the results of simultaneous testing (F test) shown in the Fcount value of (32.345) > Ftable (2.77) with a significance level of 0.000 <0.05, it can be concluded that organizational climate, work ethic and individual ability have a simultaneous and significant effect on employee performance. From the results of the partial test (t test), the Organizational Climate value tcount (5.006) > ttable (1.672), Work Ethic value tcount (4.340) > ttable (1.672) and Individual Ability tcount (2.056) > ttable (1.672). This means that organizational climate, work ethic and individual abilities have a positive and significant effect on employee performance at PT. DNR Distribution Medan Branch. From the results of the discussion of multiple linear regression Y= 0.191 + 0.424(X1) + 0.318(X2) + 0.110(X3) + ei. It can be concluded that Organizational Climate, Work Ethic and Individual Abilities have a positive and significant effect on Employee Performance at PT. DNR Distribution Medan Branch. The determinant coefficient (R Square) is 0.614. This means that 61.4% of variations in employee performance can be explained by variations in organizational climate, work ethic and individual abilities, while another 38.6% can be explained by other factors not included in this research.